Study of Community Perceptions on The Development of Mount Ijen as a Tourist Destination From Socioeconomic and Environmental Perspectives - Farid, Johan Azrul; Tika Chandrika Lestary; Amelia Wahyu Enggarwati (Universitas Negeri Surabaya, 2024)
The development of the Mount Ijen Tourism Area in Tamansari Village, Licin District, Banyuwangi Regency, has had a significant impact on the socio-economic and environmental aspects of the local community. This research aims to evaluate public perceptions of the development of the Ijen Crater tourist area. The research method used is the Interactive Model from Miles and Huberman. Data collection techniques were carried out using observation, interviews, questionnaires and documentation involving 16 research samples consisting of 10 local communities and 6 key informants. The data analysis technique uses Nvivo 12 Pro to determine the relationship between each variable. The results of the research show that there is a positive influence from the development of the Ijen Crater tourist area, namely in terms of 1) economic: income of the surrounding community increases, types of work are varied and new job opportunities are opened, 2) socio-cultural: attitudes of tolerance increase, local culture and arts become more sustainable and increased security, and 3) environment: no land conversion occurs. This research emphasizes the importance of collaboration between government, business actors and the community to achieve sustainable tourism development.